Defining correlates of protection for mammalian livestock vaccines against high-priority viral diseases - Davis, Samantha K.; Jia, Fan; Wright, Quentin G.; Islam, Md. Tanjir; Bean, Andrew; Layton, Daniel; Williams, David T.; Lynch, Stacey E. (Frontiers in Immunology, 2024)
Enhancing livestock biosecurity is critical to safeguard the livelihoods of farmers, global and local economies, and food security. Vaccination is fundamental to the control and prevention of exotic and endemic high priority infectious livestock diseases. Successful implementation of vaccination in a biosecurity plan is underpinned by a strong understanding of correlates of protectionthose elements of the immune response that can reliably predict the level of protection from viral challenge. While correlates of protection have been successfully characterized for many human viral vaccines, for many high priority livestock viral diseases, including African swine fever and foot and mouth disease, they remain largely uncharacterized. Current literature provides insights into potential correlates of protection that should be assessed during vaccine development for these high priority mammalian livestock viral diseases. Establishment of correlates of protection for biosecurity purposes enables immune surveillance, rationale for vaccine development and successful implementation of livestock vaccines as part of a biosecurity strategy.